Exploring youth participation in community development organisations in the Western Cape - Matsela, Tebatso (Department of Social Development, 2015)
The aim of the study was to explore youth participation in Community Development Organisations and its implications for positive youth development from the perspective of a select sample of Youth in the Western Cape. A purposive sample of 18 youth respondents between the ages (14-35) from five communities in the Western Cape were approached. The study used Lerner (2004) and Lerner et al.'s (2005) Positive Youth Development model (PYD), and the Critical Youth Empowerment model (CYE) by Jennings et al (2006). The study adopted a qualitative exploratory approach, using a structured interview schedule for face to face interviews with the young people. The findings revealed that young people volunteer in youth-initiated organisations within their communities because they are able to occupy instrumental roles. The findings also revealed that young people participate because they want to see positive change in their communities. Additionally, youth participation in community development has a positive impact on young people's lives (skills acquisition, personal growth, opportunities made available, connection to their communities and community members). Lastly, the findings revealed that young people are capable of making a positive contribution by getting involved in meaningful activities in their communities. The study's main recommendation is for increased efforts in education institutions, community councils and development organisations to involve young people in effective and instrumental participation in community development initiatives. Another recommendation is for the adoption of the Positive Youth Development approach in community and youth development programmes/strategies across the country.